Gender and the Faculty Care Gap: “The Obvious Go-To Person” for Canadian University Students’ Personal Problems - Dengate, Jennifer; Peter, Tracey; Farenhorst, Annemieke (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2019)
A mixed methods analysis of Canadian natural sciences and engineering faculty’s workplace experiences revealed a gendered care gap with women reporting greater responsibility for students’ personal and mental health problems, including suicidal thoughts and behaviour, and sexual assault. Statistical results demonstrated that women were approached by a significantly greater number of students to discuss serious non-academic issues and experienced more stress as a result. A comparative qualitative analysis found faculty’s responses to students’ problems were informed by gendered cultural care expectations thatrequire women to be more supportive than men. However, female and male faculty’s care burden may also be exacerbated by institutional factors, including senior administrative positions, undergraduate class loads, and teaching courses with mental health-related content. As such, the care gap is relevant to understanding the extent to which gender inequality is embedded within the structure of universities.